Improving the Performance of Internal Auditor in Implementing the Supervision Policy in Pemprov DKI Jakarta - Sjaiful, Evilina; Akbar, Maruf; ., Soetjipto (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper examines the implementation of supervision policy in DKI Jakarta Province. The research approach is qualitative using DEM (Discrepancy Evaluation Model). The method in gathering data is by observation, interview and documentation and the analysis technique is by reducing data, presenting and concluding. The research findings show: (1) In the Design Stage, the release of government policy regarding the supervision conducted by the Jakarta Intern Administration Superintendent (Inspectorate) is a process to ensure that local government run efficiently and effectively in accordance with the stipulated plan; (2) In the Installation Stage, there are two overlapping functional positions in conducting internal supervision of government administration in DKI Jakarta, namely Auditor and P2UPD (Supervisor of Administration of Government Affairs in the Local). The internal supervision of DKI Jakarta government conducted by Inspectorate (APIP) includes the organizing activities of local government and performance of local government apparatus; (3) In the Process Stage, Jakarta Inspectorate performs 3 (three) types of supervision, namely pre-audit supervision, supervision in the implementation process and post-audit supervision; (4) In the Results Stage, the level of Inspectorate performance in 2015 in conducting supervision has not achieved 100% target, as measured from: (a) index of Jakarta DKI Corruption Perception reached 3.4 out of 3.8 target (b) assessment of financial statements with fair opinion results with exception (WDP) from unqualified target (WTP) and (c) Indicator of Improvement assessed by LKIP achieved CC from B target.